# (a-b)(a^2ab+b^2)

Input |
---|

(a – b) (a^2 a b + b^2) |

Result |

(a – b) (a^3 b + b^2) |

Expanded form |

a^4 b – a^3 b^2 + a b^2 – b^3 |

Alternate form assuming a and b are positive |

b (a^4 – a^3 b + a b – b^2) |

Real root |

b = 0 |

Polynomial discriminant |

Delta_a = -27 b^6 (b^4 + b^2)^2 |

Property as a function |

odd |

Derivative |

(d)/(da)((a – b) (a^2 a b + b^2)) = b (4 a^3 – 3 a^2 b + b) |

Indefinite integral |

integral (a – b) (a^3 b + b^2) da = b (a^5/5 – (a^4 b)/4 + (a^2 b)/2 – a b^2) + constant |